A Development of E-Learning-Based Instructional Media for English At Medan Civil Aviation Academy - Tiara Sylvia; Liber Tommy Hutabarat (Data Science: Journal of Computing and Applied Informatics, 2021)
The research aims to: (1) give comprehension of the concept of E-Learning as an instructional media; (2) develop E-Learning based instructional media for English; (3) know the effectiveness of E-Learning as an instructional media to improve cadets’ skill in English. E-Learning based instructional media was developed in Learning Management System (LMS) of Medan Civil Aviation Academy consisting of applicable features to be used easily and effectively by lecturer and cadets based on Elementary English lesson plan. The research was conducted at Medan Civil Aviation Academy in the odd semester of 2019/2020 academic year. The population was 144 cadets of first year and 24 cadets were taken as the sample through cluster random sampling technique. The method used in this research was research and development method and the technique of collecting data were by test and questionnaire.The results of the research concluded that: (1) cadets conducting E-Learning based instructional media achieved higher score (70,10) than conventional method (56,67); (2) development of E-Learning based instructional media showed high effectiveness in learning process gained from valid and reliable questionnaire (r11 = 0.8205); (3) development of E-Learning based instructional media was stated in “ a very good category” in term of usability aspect.